Use of cellular biotechnologies in treatment metastatic pericarditis at patients with tumors of female reproductive system - K. S. Titov; S. M. Volkov; L. V. Demidov; A. N. Gritsay; N. I. Lazareva; M. V. Kiselevskiy; A. P. Nikolayev (ABV-press, 2014)
Malignant pericardial effusions often arise in patients with breаst cancer and ovarian cancer. Sistem antitumor therapy is uneffective in gen- erally and causes side effects. Here we show that intrapericardial interleukin-2 with allogenеc lymphokine-activated killers and interleukin-2 immunotherapy demonstrated the high efficacy in threatment of breаst and ovarian cancer patients with malignant pericardial effusions. The objective effect was 92.3 % аnd 90.0 % accordingly. These results indicates that intrapericardial immunotherapy might be one of the stages of combined treatment of such group of patients. The suggested type of biotherapy increases the survival and life quality of patients.